The Indonesia-Australia Cooperation In Responding To The Covid-19 Pandemic (2020) - Mentari Mentari (Jurnal Indonesia Sosial Teknologi, 2021)
The COVID-19 pandemic began in Wuhan, China in late December 2019 and rapidly spread to all over the world. The COVID-19 caused by SARS-Cov-2 and more than one million people have been affected worldwide. The COVID-19 pandemic not only impacts the health sector, but the pandemic triggered to the economic crisis with expansive social effects. Due to the impact of COVID-19, the international cooperation needs to be taken to responding and control the pandemic. Indonesia and Australia as a close neighbour, have worked closely in disaster risk management and currently cooperate to response the COVID-19. This study aims to describe the cooperation between Indonesia and Australia in responding the impacts of COVID-19. This study uses a qualitative approach with descriptive method. The data collection technique used based on secondary data in the form of literature review (library research) including books, journals, reports, organization’s websites, online articles, and scientific papers that are related to the study. The author uses the concept of cooperation to support the idea of cooperation between Indonesia and Australia to responding the impacts of COVID-19 pandemic. This study provides that the cooperation between Indonesia and Australia in responding the impacts of COVID-19 are divided into three sectors, namely health security, stability, and economic recovery.